Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex]x^2-4x+2=0 \\ \\
a=1 \\ b=-4 \\ c=2 \\ b^2-4ac=(-4)^2-4 \times 1 \times 2=16-8=8 \\ \\
x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}=\frac{-(-4) \pm \sqrt{8}}{2 \times 1}=\frac{4 \pm \sqrt{4 \times 2}}{2}=\frac{4 \pm 2\sqrt{2}}{2}=\frac{2(2 \pm \sqrt{2})}{2}=2 \pm \sqrt{2} \\
\boxed{x=2-\sqrt{2} \hbox{ or } x=2+\sqrt{2}}[/tex]
[tex]x^2-4x+2=0\\x^2-4x+4-2=0\\
(x-2)^2=2\\
x-2=\sqrt2 \vee x-2=-\sqrt2\\
x=2+\sqrt2 \vee x=2-\sqrt2[/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.